Virtual farm tours—Virtual reality glasses and tablets are suitable tools to provide insights into pig husbandry - Schütz, Aurelia; Kurz, Katharina; Busch, Gesa (PLOS ONE, 2022)
Apart from improving husbandry conditions and animal welfare, there is a clear public demand to increase transparency in agricultural activities. Personal farm tours have shown to be appreciated by citizens but are limited in their impact because of hygiene requirements and accessibility. Virtual farm tours are a promising approach to overcome these limitations but evidence on their perceptions is missing. This study analyzes how a virtual farm tour is perceived by showing participants (n = 17) a 360-degree video of a conventional pig fattening pen on a tablet and via virtual reality (VR) glasses. Semi-structured in-depth interviews were conducted to analyze perceptions and level of immersion and to elicit differences between media devices. Participants’ perception of the pig fattening pen was rather poor and depended on the recording perspective as well as on the media device. However, housing conditions were perceived more positively compared to the image participants had in mind prior to the study, and thus the stable was considered as a rather positive example. Participants described virtual farm tours as suitable tool to improve transparency and information transfer and to gain insights into husbandry conditions. They appreciated the comfortable and entertaining character of both media devices and named various possibilities for implementation. However, VR glasses were favored regarding the higher realistic and entertaining value, while the tablet was considered beneficial in terms of usability. The presentation of video sequences without additional explanations about the farm or the housing conditions were claimed insufficient to give an adequate understanding of the seen content.